DETERMINING THE STRESS FIELD IN EARTH’S CRUST FROM SOURCE MECHANISMS OF LOCAL EARTHQUAKES IN THE TRANSCARPATIANS - Malytskyy, D.; Murovska, A.; Obidina, O.; Gnyp, A.; Grytsai, O.; Pavlova, A.; Pugach, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In the paper, 20 source mechanisms of local earthquakes in the Transcarpathians were determined for the first time, which is very important for further geodynamic modeling. Focal mechanisms of earthquakes for the period from 2012 to 2015 were determined using a graphic method. The parameters of source mechanism of 23.10.06 earthquake near the city of Berehove (magnitude MSH 3.7) were also taken from earlier publications. Subsequently, after a general statistical and typification analysis of 21 mechanisms the characteristics of stress-strained state were identified, prevalent in the entire region. Depended on orientation of cinematic axes, the focal mechanisms were separated into three groups corresponding to thrusting, normal faulting and strike-slip types. The majority of the studied mechanisms belonged to strike-slip and thrusting types, almost all strike-slip mechanisms containing a component of thrusting. Two methods were employed in our work to determine stress field from mechanisms of local earthquakes in the Transcarpathians. In the first one, suggested by Michael (1984) and further developed in works of Vavrychuk, stress tensor was determined from focal mechanisms. The other one was a so called method of PT-axes. It is usually assumed in both methods that: 1) tectonic stress is uniform (homogeneous) in the region, 2) earthquakes occur on pre-existing faults with varying orientations and 3) the slip vector points in the direction of shear stress on the fault (the so called Wallace-Bott hypothesis). To calculate the stress field by method of PT-axes program WIN-TENSOR was used. Results, presented in the paper, definitely indicate prevalence of contraction in the study region. In the contraction field SW 250, prevailing in almost entire study region, two anomalous zones were identified: the first one, extended along the SW boundary of Chop-Mukacheve depression, with two directions of contraction in it; the second one, in the eastern part of Solotvyno depression, with extension conditions in the SW direction, contraction prevailing at the same time in SW direction in the most part of the Transcarpathian through (TT). Analysis of 42 nodal plain orientations confirmed the most active role of ruptures parallel to the Carpathian extension in present seismotectonic process. Another distinction of the local sources consists in a fact that earthquakes of adverse types (thrusting and faulting, for instance) often occur in the same area, very close to each other, which can be considered logical since extension conditions arise in the rear zone of thrusts in the same direction as contraction in their frontal part.